Long-term detection of atrial fibrillation with insertable cardiac monitors in a real-world cryptogenic stroke population. (1st October 2017) - Ziegler, Paul D.; Rogers, John D.; Ferreira, Scott W.; Nichols, Allan J.; Richards, Mark; Koehler, Jodi L.; Sarkar, Shantanu
ABSTRACT: Background: The long-term incidence of atrial fibrillation (AF) in cryptogenic stroke (CS) patients has been explored in carefully controlled clinical trials but real-world data are limited. We investigated the two-year incidence of AF in real-world clinical practice among a large cohort of patients with an insertable cardiac monitor (ICM) placed for AF detection following CS. Methods: Patients in the de-identified Medtronic Discovery™ Link database who received an ICM (Reveal LINQ™) for the purpose of AF detection following CS were included and monitored for up to 2 years. All detected AF episodes (≥ 2 min) were adjudicated. We quantified the AF detection rate using Kaplan-Meier survival estimates, analyzed the median time to initial detection of AF, and simulated the ability of various intermittent monitoring strategies to detect AF. Results: A total of 1247 patients (65.3 ± 13.0 years, 53% male) were included and followed for 579 ± 222 days. AF episodes (n = 4183) were detected in 238 patients, resulting in an AF detection rate of 21.5% at 2 years. The median time to AF detection was 112 [IQR 35–293] days. Intermittent monitoring for AF detection was inferior to continuous ICM monitoring with sensitivities ranging from 2.9% (annual 24-hour Holter) to 29.9% (quarterly 7-day Holters), p < 0.001. Conclusions: AF episodes were detected via continuous monitoring with ICMs in approximately 1 of every 5 CS patients within 2 years of follow-up. The vast majority of patients with AF would not have been detected with conventional external ambulatory monitors. ICMs should therefore be considered in the evaluation of CS patients.